محشر رسول نگری کی نعتیہ شاعری: "فخر کونین" کے تناظر میں: The Naatiya Poetry of the Resurrected Rasool Nagri: In the Context of "Fakhr-e-Kunin" - Iqbal, Nasar (Zoraiz, 2025)
Na’at writing is a great blessing. After the birth of the Holy Prophet (PBUH) countless poets have been experimenting in this genre of speech. But the historical facts show that this subject is not so easy that everyone can get competent in this genre. Therefore it can be said that for creating Na’at along with being a lover of Prophet (PBUH) it is also necessary to have knowledge about Tauheed, Prophethood and Maqam e Mustafa (SAW). The history of creating Na’at is as old as the history of Urdu literature. Nisar Ahmad, Mehshar Rasool Nagri was a famous poet. He was born in a noble family of Balochistan, province of Pakistan. When we look at his family background he was the luminary of a noble family. The beginning of his poetry is proven from his student age. Along with poetry he was also a proficient prose writer. The most important achievement of Mehshar Rasool Nagri is the publication of “Fakhr e Kounain” in verse form as a biography of The Prophet (PBUH). “Fakhr e Kounain” is the biography of Rasool-e-Kareem (SAW) in three volumes. In this article, an intellectual and a technical review is being presented regarding Mehshar Rasool Nagri’s Na’atiya Kalaam.